Income adequacy in retirement: Evidence from the Irish longitudinal study on ageing (TILDA) - Keelan Beirne; Anne Nolan; Barra Roantree (The Economic and Social Research Institute (ESRI), 2020)
Those who are not married or cohabitating in the years before retirement are at greater risk of having inadequate income in retirement, according to a new study published today by the Economic and Social Research Institute (ESRI).
Keywords: 330; Ehe; Rentenpolitik; Rentenfinanzierung; Einkommenseffekt; Längsschnittanalyse; Irland